Gene targeting in melanoma therapy: exploiting of surface markers and specific promoters - Alekseenko, I.V.; Zinovyeva, M.V.; Pleshkan, V.V.; Sverdlov, E.D. (Вiopolymers and Cell, 2012)
One of the problems of gene therapy of melanoma is effective expression of therapeutic gene in tumor cells and their metastases but not in normal cells. In this review, we will consider a two-step approach to a highly specific gene therapy. At the first step, therapeutic genes are delivered specifically to tumor cells using cell surface markers of melanoma cells as targets. At the second step, a specific expression of the therapeutic genes in tumor cells is ensured. Surface markers of melanoma cells were analyzed as potential targets for therapeutic treatment. Criteria for choosing the most promising targets are proposed. The use of specific melanoma promoters allows to further increase the specificity of treatment via transcriptional control of therapeutic gene expression in melanoma cells. Одной из проблем генной терапии злокачественной меланомы является целенаправленная экспрессия терапевтического гена в опухолевых клетках и их метастазах при минимизации ее в нормальных клетках. В обзоре рассмотрен двухэтапный подход к высокоспецифичной терапии. На первом этапе осуществляется адресная доставка терапевтических генов в опухолевые клетки с использованием в качестве мишени поверхностных маркеров меланомных клеток, на втором – обеспечивается специфичность экспрессии генов в опухолевых клетках. Проведен анализ поверхностных маркеров меланомных клеток с точки зрения применения их как мишеней для терапевтического воздействия. Предложены критерии выбора наиболее перспективных мишеней. Использование промоторов, активных только в меланомных клетках, позволяет еще больше увеличить специфичность воздействия за счет контроля транскрипции терапевтических генов в таких клетках. Однією з проблем генної терапії злоякісної меланоми є цілеспрямована експресія терапевтичного гена в пухлинних клітинах і їхніх метастазах за мінімізації її у нормальних клітинах. В огляді розглянуто двоетапний підхід до високоспецифічної терапії. На першому етапі здійснюється адресна доставка терапевтичних генів у пухлинні клітини з використанням як мішені поверхневих маркерів меланомних клітин, на другому – забезпечується специфічність експресії генів у пухлинних клітинах. Проведено аналіз поверхневих маркерів меланомних клітин з точки зору застосування їх як мішеней для терапевтичної дії. Запропоновано критерії вибору найперспективніших мішеней. Використання промоторів, активних лише в меланомних клітинах, дозволяє збільшити специфічність дії за рахунок контролю транскрипції терапевтичних генів у таких клітинах.